2018
DOI: 10.1016/j.coesh.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Beyond opposition and acceptance: Examining public perceptions of the environmental and health impacts of unconventional oil and gas extraction

Abstract: CLoK Central Lancashire online Knowledge www.clok.uclan.ac.uk Beyond opposition and acceptance: examining public perceptions of the environmental and health impacts of unconventional oil and gas extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…For example, Aitken (2010Aitken ( p. 1834Aitken ( , 1840 draws out the assumptions which underlie social acceptance literature and suggests that researchers should not be contributing to advancing the social acceptance of energy technologies. As such, some scholars have moved beyond a focus on 'acceptance' and have instead focused on general and varied responses to energy infrastructure (i.e., see Cotton and Charnley-Parry 2018). Aitken (2010Aitken ( , p. 1838) critiques research that aims to reduce opposition and increase the likelihood of planning approval of energy projects by questioning: (1) what is considered the 'problem' and who decides this, (2) what conclusions are drawn, and (3) how this approach may gloss over the legitimate and valid community concerns about a proposed energy project.…”
Section: Instrumental Rationale In Social Science Energy Researchmentioning
confidence: 99%
“…For example, Aitken (2010Aitken ( p. 1834Aitken ( , 1840 draws out the assumptions which underlie social acceptance literature and suggests that researchers should not be contributing to advancing the social acceptance of energy technologies. As such, some scholars have moved beyond a focus on 'acceptance' and have instead focused on general and varied responses to energy infrastructure (i.e., see Cotton and Charnley-Parry 2018). Aitken (2010Aitken ( , p. 1838) critiques research that aims to reduce opposition and increase the likelihood of planning approval of energy projects by questioning: (1) what is considered the 'problem' and who decides this, (2) what conclusions are drawn, and (3) how this approach may gloss over the legitimate and valid community concerns about a proposed energy project.…”
Section: Instrumental Rationale In Social Science Energy Researchmentioning
confidence: 99%
“…Public perceptions. These studies examine the demographic characteristics (Thomas et al, 2017), political ideologies, and technical knowledge (Crowe et al, 2015;Evensen et al, 2017;Lachapelle, 2017) of supporters and opponents (Cotton and Charnley-Parry, 2018), the conditions under which risks are perceived and negotiated (Whitmarsh et al, 2015), and the commonalities and shared interpretations of UHD discourse within and amongst different stakeholder groups (Cotton, 2015;Ladd, 2013).…”
Section: Discourses Of Unconventional Oil and Gas Developmentmentioning
confidence: 99%
“…Moreover, in terms of the reasons for opposing/supporting fracking, the empirical literature has often found, not surprisingly, that respondents who expect fracking to deliver economic benefits to their region are more supportive of the practice, while those who fear environmental or health issues are much less supportive of drilling (Theodori, 2009;Jacquet, 2012;Kriesky et al, 2013;Jacquet, 2014;Boudet et al, 2014;Graham et al, 2015;Whitmarsh et al, 2015;Andersson-Hudson et al, 2016;Boudet et al, 2016;Whitworth et al, 2017;Cotton and Charnley-Parry, 2018). For instance, Boudet et al (2016) found that employment levels in the natural resources and mining sector in the respondents county, as well as residing in an area experiencing active OG development, significantly increase support for fracking.…”
Section: Previous Work On Attitudes Towards Frackingmentioning
confidence: 99%